Firm-specific demands on open source software communities (OSC): Elucidating the problem generation mechanism focusing on organizational characteristics of OSCs - Yoshihide SHIMADA; Taichi KISHIMOTO (AAOS Transactions)
In this study, based on the insights from the case study, we discuss the causes and mechanisms of problems arising from firms’ custom orders to OSCs, focusing on the organizational characteristics of OSCs, and propose hypotheses. Since the 21st century, the main field of software development has shifted from corporate R&D departments to OSCs. The use of Linux in smartphone operating system is a prime example of this. When firms utilize OSS, custom orders by forms are necessary. Most of the research dealing with problems and their causes when firms place custom orders with OSCs has focused on the organizational characteristics of the firms themselves. However, in the cases we examined, we observed phenomena suggesting that the cause of the problem lies in the organizational characteristics of the OSCs rather than the firms. As a result of the research, three key characteristics were identified as the main causes of the problems: “loose network of independent technical managers”, “technical self-realization as the fundamental principle of decision-making”, and “abandonment of planning and control”. In addition, the logical hypothesis was presented following the OCP （Organizational Characteristic-Conduct-Problem） framework.